Curfew for Anniversary of Odessa Massacre That Sparked Rebellion (2022)
Odessa has imposed a two-day curfew on the anniversary of the burning alive of anti-Maidan protestors on May 2, 2014, reports Joe Lauria. https://www.youtube.com/watch?v=vy-YrTdt7RE By Joe Lauria Special to Consortium News Authorities in the Ukrainian port city of Odessa have set a 24-hour
Section: European Union